High-entropy nano array for electro-catalysis nitrate radical reduction coupling waste plastic conversion and preparation method of high-entropy nano array

Through high-entropy nanoarrays as electrocatalysts, the problem of treating nitrate-containing wastewater and PET waste plastics in the prior art is solved, efficient electrocatalytic conversion is achieved, and environmental governance and resource utilization efficiency is improved.

CN119465252AActive Publication Date: 2025-02-18ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411415537.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-18
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat nitrate-containing industrial wastewater and PET waste plastics, resulting in environmental pollution and health hazards.

Method used

High entropy nanoarrays are used as electrocatalysts and are prepared by a simple one-step wet chemistry method for electrocatalytic nitrate reduction and upgrade conversion of PET waste plastics.

Benefits of technology

High entropy nanoarrays exhibit excellent electrocatalytic activity and stability in novel coupling systems, enabling efficient conversion of nitrate wastewater and PET waste plastics into value-added chemicals such as ammonia and glycolic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465252A_ABST
    Figure CN119465252A_ABST
Patent Text Reader

Abstract

A high-entropy nano array for electro-catalysis nitrate radical reduction coupling waste plastic conversion is prepared by the following steps: (1) immersing foamed nickel into a hydrochloric acid solution to remove a surface oxide layer and oil stain, washing the foamed nickel with deionized water / ethanol for three times, and drying the foamed nickel for subsequent use; (2) pouring solid powder of sodium chloropalladate, platinum acetylacetonate, nickel chloride hexahydrate, copper chloride dihydrate, silver trifluoroacetate and tungsten hexacarbonyl into an N-N dimethylformamide solution, carrying out ultrasonic treatment to dissolve the solid powder, then adding glacial acetic acid and the treated foamed nickel into the solution, carrying out ultrasonic treatment, heating in a drying oven, and carrying out vacuum drying to obtain the nickel-based composite material. And after the reaction is finished, alternately washing with water and an ethanol solution, and drying to obtain the high-entropy nano array catalyst. The invention further provides a preparation method of the high-entropy nano array for electro-catalysis nitrate radical reduction coupling waste plastic conversion. The high-entropy nano array disclosed by the invention has excellent electrocatalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high entropy nano array and a preparation method thereof. The material can be used for research on a novel coupling system of nitrate reduction and waste plastic conversion. Background Art

[0002] The accumulation of nitrate-containing industrial wastewater and polyethylene terephthalate (PET) waste plastics in nature has caused a series of environmental problems and caused harm to human health. To effectively deal with this situation, a feasible strategy is to upgrade and recycle polluted waste into value-added chemicals to realize waste resource utilization. Among various upgrading and recycling technologies, electrocatalysis technology is a green and sustainable solution. This technology is driven by renewable electricity and operates under mild conditions. It can efficiently and synchronously convert nitrate wastewater and PET waste plastics into value-added chemicals such as ammonia and glycolic acid. Therefore, the design of electrocatalysts with excellent performance plays a decisive role in the upgrading and conversion of nitrate wastewater and PET waste plastics.

[0003] High entropy alloys (HEAs) are novel and unique multimetallic alloys composed of five or more elements. Due to their unique advantages such as high entropy effect, lattice distortion effect and "cocktail" effect, HEAs have attracted extensive attention in electrocatalytic applications. The presence of multiple adjacent elements in HEAs can create new active sites with unique properties, which can be optimized for specific performance by precisely selecting specific elements and compositions. Therefore, a reasonable design strategy is crucial to improve the catalytic performance of HEAs for specific reactions. Electrocatalysts with ultrathin sheet morphology exhibit excellent electrocatalytic performance due to their structural anisotropy, rich surface chemistry and efficient electron diffusion ability. Therefore, combining the multi-element properties of HEAs and the unique structural advantages of ultrathin two-dimensional nanosheets, constructing high entropy nanoarrays is a new direction for the development of advanced high entropy alloy electrocatalysts. The design of high entropy nanoarray catalysts provides a unique possibility for a new coupling system for the electrocatalytic upgrading of nitrate wastewater and PET waste plastics. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a high entropy nanoarray, and studies the performance of a novel coupling system for electrocatalytically upgrading nitrate wastewater and PET waste plastics.

[0005] The technical solution adopted by the present invention is:

[0006] A high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion is prepared by the following method:

[0007] (1) Immerse 1-2 cm × 1-2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0008] (2) Pour 10-20 mg of solid powders of sodium chloropalladate, 5-10 mg of platinum acetylacetonate, 5-10 mg of nickel chloride hexahydrate, 1-3 mg of cupric chloride dihydrate, 1-3 mg of silver trifluoroacetate and 10-20 mg of tungsten hexacarbonyl into 4-8 mL of N-N-dimethylformamide solution, ultrasonicate for 10-20 minutes to dissolve the solid powders, then add 1-2 mL of glacial acetic acid and the treated nickel foam to the solution, ultrasonicate for 3-5 minutes, and then heat in an oven at 120-160° C. for 4-12 hours; after the reaction is completed, wash alternately with water and ethanol solution, and dry to obtain the catalyst.

[0009] In the present invention, a typical high entropy nanoarray is prepared by a simple one-step wet chemical method. During the synthesis process, the carbon monoxide decomposed by tungsten hexacarbonyl in the system under high temperature conditions acts as a directing agent for the sheet structure to induce the generation of a two-dimensional structure. At the same time, nickel foam is used as a carrier and palladium, platinum, copper, nickel and silver precursors are reduced by glacial acetic acid to form a two-dimensional high entropy nanosheet array.

[0010] A method for preparing a high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion comprises the following steps:

[0011] (1) Immerse 1-2 cm × 1-2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0012] (2) Pour 10-20 mg of solid powders of sodium chloropalladate, 5-10 mg of platinum acetylacetonate, 5-10 mg of nickel chloride hexahydrate, 1-3 mg of cupric chloride dihydrate, 1-3 mg of silver trifluoroacetate and 10-20 mg of tungsten hexacarbonyl into 4-8 mL of N-N-dimethylformamide solution, ultrasonicate for 10-20 minutes to dissolve the solid powders, then add 1-2 mL of glacial acetic acid and the treated nickel foam to the solution, ultrasonicate for 3-5 minutes, and then heat in an oven at 120-160° C. for 4-12 hours; after the reaction is completed, wash alternately with water and ethanol solution, and dry to obtain the catalyst.

[0013] The new coupling performance test of electrocatalytic nitrate wastewater and PET waste plastic upgrading and conversion was carried out at room temperature and pressure. The specific operation process is as follows:

[0014] (1) Preparation of PET degradation electrolyte: 50-100 g of waste plastic was poured into 100-200 mL of 4-8 M potassium hydroxide solution and continuously stirred in a 60° C. oil bath for 48-72 hours for degradation. After degradation, the PET degradation liquid was obtained by filtration for use.

[0015] (2) Cathodic electrocatalytic nitrate reduction test: The prepared catalyst was used as the working electrode, the carbon rod as the counter electrode, and the Hg / HgO electrode as the reference electrode to form a three-electrode system. The cathodic electrocatalytic nitrate reduction performance was tested in a mixed solution of 0.1-1M potassium hydroxide and 0.1-1M potassium hydroxide + 0.1-1M potassium nitrate. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. UV-visible spectrophotometer and nuclear magnetic resonance were used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of nitrate reduction to ammonia on the high entropy nanoarray were comprehensively evaluated. All potentials in this work were converted to relative to the standard hydrogen electrode.

[0016] (3) Anodic electrocatalytic PET degradation liquid oxidation test: The prepared catalyst was used as the working electrode, the carbon rod was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode to form a three-electrode system. The anodic electrocatalytic PET degradation liquid oxidation performance test was carried out in 0.1-1M potassium hydroxide and PET degradation liquid. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. Nuclear magnetic resonance was used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of PET degradation liquid oxidation to glycolic acid on the high entropy nanoarray were comprehensively evaluated. All potentials in this work were converted to relative to the standard hydrogen electrode.

[0017] (4) Test of electrocatalytic coupling system: The prepared catalyst was used as cathode and anode respectively, and the electrolytes in the cathode chamber and anode chamber were 0.1-1M potassium hydroxide + 0.1-1M potassium nitrate mixed solution and PET degradation solution respectively to form a new coupling system. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. UV-visible spectrophotometer and nuclear magnetic resonance were used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of cathode nitrate reduction to generate ammonia and anode PET degradation solution oxidation to generate glycolic acid on the high entropy nanoarray were comprehensively evaluated.

[0018] The beneficial effects of the present invention are mainly manifested in: (1) a typical high entropy nanoarray is successfully prepared by a one-pot wet chemical method, and its application in a novel coupling system is demonstrated. (2) the high entropy nanoarray exhibits excellent cathode electrocatalytic nitrate reduction and anode electrocatalytic PET degradation liquid oxidation performance in the novel coupling system, and has excellent electrocatalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 These are scanning electron microscope images and transmission electron microscope images of the high entropy nanoarray according to specific embodiment 1 of the present invention.

[0020] Figure 2 This is an X-ray diffraction diagram of the high entropy nanoarray according to specific embodiment 1 of the present invention.

[0021] Figure 3 is the atomic percentage of the high entropy nanoarray in specific embodiment 1 of the present invention.

[0022] Figure 4 This is a linear sweep voltammetric curve of the cathode electrocatalytic nitrate reduction of the high entropy nanoarray according to the specific embodiment 1 of the present invention.

[0023] Figure 5 This is the Faradaic efficiency and yield of ammonia produced by cathode electrocatalytic reduction of nitrate at different voltages using the high entropy nanoarray in specific embodiment 1 of the present invention.

[0024] Figure 6 This is a linear sweep voltammetric curve of the anode electrocatalytic oxidation of PET degradation liquid by the high entropy nanoarray in specific embodiment 1 of the present invention.

[0025] Figure 7 This is the Faradaic efficiency and yield of PET degradation liquid oxidized to glycolic acid by the anode electrocatalysis at different potentials of the high entropy nanoarray in specific embodiment 1 of the present invention.

[0026] Figure 8 This is a linear sweep voltammetric curve of the coupling system of the high entropy nanoarray of the specific embodiment 1 of the present invention.

[0027] Fig. 9 This is the Faraday efficiency and yield of the cathode and anode of the coupling system under different voltages of the high entropy nanoarray of the specific embodiment 1 of the present invention.

[0028] Fig.10 This is a stability test of the high entropy nanoarray coupling system of specific embodiment 1 of the present invention.

[0029] Fig.11 The scanning electron microscope image and the transmission electron microscope image of the high entropy nanoarray according to the specific embodiment 2 of the present invention are shown.

[0030] Fig.12 is the atomic percentage of the high entropy nanoarray according to specific embodiment 2 of the present invention.

[0031] Fig.13 This is a linear sweep voltammetric curve of the coupling system of the high entropy nanoarray of specific embodiment 2 of the present invention.

[0032] Fig.14 These are scanning electron microscope images and transmission electron microscope images of the high entropy nanoarray according to specific embodiment 3 of the present invention.

[0033] Fig.15 It is the atomic percentage of the high entropy nanoarray in specific embodiment 3 of the present invention.

[0034] Fig.16 The linear sweep voltammetric curves of three high entropy nanoarray coupling systems are specific embodiments of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0036] Reference Figures 1 to 10 , a high entropy nanoarray for electrocatalytic nitrate reduction coupled to waste plastic conversion, prepared by the following method:

[0037] (1) Immerse 1-2 cm × 1-2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0038] (2) Pour 10-20 mg of solid powders of sodium chloropalladate, 5-10 mg of platinum acetylacetonate, 5-10 mg of nickel chloride hexahydrate, 1-3 mg of cupric chloride dihydrate, 1-3 mg of silver trifluoroacetate and 10-20 mg of tungsten hexacarbonyl into 4-8 mL of N-N-dimethylformamide solution, ultrasonicate for 10-20 minutes to dissolve the solid powders, then add 1-2 mL of glacial acetic acid and the treated nickel foam to the solution, ultrasonicate for 3-5 minutes, and then heat in an oven at 120-160° C. for 4-12 hours; after the reaction is completed, wash alternately with water and ethanol solution, and dry to obtain the catalyst.

[0039] The high entropy nanoarray coupling performance test of this embodiment was carried out on a CHI 760E electrochemical workstation, and the operation process was as follows:

[0040] (1) Preparation of PET degradation electrolyte: 50-100 g of waste plastic was poured into 100-200 mL of 4-8 M potassium hydroxide solution and continuously stirred in a 60° C. oil bath for 48-72 hours for degradation. After degradation, the PET degradation liquid was obtained by filtration for use.

[0041] (2) Cathodic electrocatalytic nitrate reduction test: The prepared catalyst was used as the working electrode, the carbon rod as the counter electrode, and the Hg / HgO electrode as the reference electrode to form a three-electrode system. The cathodic electrocatalytic nitrate reduction performance was tested in a mixed solution of 0.1-1M potassium hydroxide and 0.1-1M potassium hydroxide + 0.1-1M potassium nitrate. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. UV-visible spectrophotometer and nuclear magnetic resonance were used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of nitrate reduction to ammonia on the high entropy nanoarray were comprehensively evaluated. All potentials in this work were converted to relative to the standard hydrogen electrode.

[0042] (3) Anodic electrocatalytic PET degradation liquid oxidation test: The prepared catalyst was used as the working electrode, the carbon rod was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode to form a three-electrode system. The anodic electrocatalytic PET degradation liquid oxidation performance test was carried out in 0.1-1M potassium hydroxide and PET degradation liquid. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. Nuclear magnetic resonance was used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of PET degradation liquid oxidation to glycolic acid on the high entropy nanoarray were comprehensively evaluated. All potentials in this work were converted to relative to the standard hydrogen electrode.

[0043] (4) Test of electrocatalytic coupling system: The prepared catalyst was used as cathode and anode respectively, and the electrolytes in the cathode chamber and anode chamber were 0.1-1M potassium hydroxide + 0.1-1M potassium nitrate mixed solution and PET degradation solution respectively to form a new coupling system. Linear sweep voltammetry, cyclic voltammetry, chronoamperometry, chronovoltammetry and other methods were used for testing. UV-visible spectrophotometer and nuclear magnetic resonance were used for product detection. The electrochemical active area of ​​the high entropy nanoarray, the proportion of each product in the total product, the ratio of the charge consumed in the generation process of each product to the total charge of the working electrode, the duration of the catalytic effect and other parameters were systematically investigated. The catalytic activity, selectivity, Faraday efficiency and catalytic stability of the reaction of cathode nitrate reduction to generate ammonia and anode PET degradation solution oxidation to generate glycolic acid on the high entropy nanoarray were comprehensively evaluated.

[0044] Embodiment 1:

[0045] A method for preparing a high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion, the method comprising the following steps:

[0046] (1) Immerse 1 cm × 1 cm nickel foam in hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0047] (2) Pour 10 mg of solid powders of sodium chloropalladate, 5 mg of platinum acetylacetonate, 5 mg of nickel chloride hexahydrate, 1 mg of cupric chloride dihydrate, 1 mg of silver trifluoroacetate and 10 mg of tungsten hexacarbonyl into 4 mL of N-N-dimethylformamide solution and ultrasonicate for 10 minutes to dissolve the solid powders. Then, add 1 mL of glacial acetic acid and the treated nickel foam to the solution and ultrasonicate for 3 minutes. Then, heat in an oven at 120° C. for 4 hours. After the reaction is completed, wash alternately with water and ethanol solution and dry to obtain a high entropy nanoarray catalyst.

[0048] The scanning electron microscope image and transmission electron microscope image of the high entropy nanoarray obtained in Example 1 are shown in FIG. Figure 1 The X-ray diffraction pattern of the high entropy nanoarray obtained in Example 1 is shown in Fig. Figure 2 The atomic percentage of the high entropy nanoarray obtained in Example 1 is referenced to Figure 3 Specific Example 1 The linear sweep voltammetric curve of cathode electrocatalytic nitrate reduction of high entropy nanoarray is shown in Fig. Figure 4 Specific Example 1 The Faraday efficiency and yield of the cathode electrocatalytic reduction of nitrate to generate ammonia under different voltages of the high entropy nanoarray are obtained. Figure 5 The linear sweep voltammetric curve of the electrocatalytic oxidation of PET degradation liquid by the anode of the high entropy nanoarray obtained in Example 1 is shown in FIG. Figure 6 Specific Example 1 The Faraday efficiency and yield of the anodic electrocatalytic oxidation of PET degradation liquid to generate glycolic acid under different potentials of the high entropy nanoarray are obtained. Figure 7 The linear sweep voltammetric curve of the coupling system of the high entropy nanoarray obtained in the specific embodiment 1 is shown in FIG. Figure 8 Specific Example 1 The Faraday efficiency and yield of the cathode and anode of the coupling system under different voltages of the high entropy nanoarray are obtained. Fig. 9 Specific Example 1 Stability test of high entropy nanoarray coupling system Fig.10 .

[0049] First, the morphology and structure of the prepared high entropy nanoarrays were characterized by scanning and transmission electron microscopy. The scanning electron microscope image proved that the sample was composed of nanosheet arrays. From the transmission electron microscope image, it was more clearly observed that the high entropy nanoarray was an ultra-thin two-dimensional nanosheet. Further, through the X-ray diffraction pattern, it was observed that a typical single-phase face-centered cubic structure was shown, indicating the formation of a high entropy alloy. The scanning electron microscope energy spectrum shows the uniform distribution of Pd, Pt, Cu, Ni and Ag elements in the high entropy nanoarray. Next, the cathode electrocatalytic nitrate reduction and the anodic electrocatalytic PET degradation liquid oxidation of the high entropy nanoarray and the coupling system performance were investigated respectively. First, through the linear scanning voltammetry curve of nitrate reduction in alkaline, it can be observed that the high entropy nanoarray exhibits a higher current density in the electrolyte with potassium nitrate added, indicating that the high entropy nanoarray has a high catalytic activity for nitrate reduction. In an electrolyte containing 1M potassium hydroxide + 0.1M potassium nitrate, the high entropy nanoarray has an ammonia yield of 0.4mmol h at a low voltage (-0.15V vs.Hg / HgO). -1 cm -2, the Faraday efficiency of ammonia reached 96.0%, indicating that the high entropy nanoarray has a better activity in synthesizing ammonia by nitrate reduction. Next, through the linear sweep voltammetric curve of PET degradation solution oxidation under alkaline conditions, it can be observed that the high entropy nanoarray exhibits a higher current density in the PET degradation solution, indicating that the high entropy nanoarray also has a high catalytic activity for the oxidation of PET degradation solution. The high entropy nanoarray has a glycolic acid yield of 1.5 mmol h at low voltage (0.8 V vs. Hg / HgO). -1 cm -2 , the Faradaic efficiency of glycolic acid reached 97.2%, indicating that the high-entropy nanoarray also has a better activity in synthesizing glycolic acid from PET degradation solution oxidation. Therefore, we tested the electrochemical performance of the high-entropy nanoarray in a new coupling system consisting of cathode nitrate reduction and anode PET degradation solution oxidation. The linear sweep voltammetry curve shows that compared with the traditional water electrolysis, the high-entropy nanoarray only requires a lower voltage to achieve the same current density in the new coupling system. In the new coupling system, the high-entropy nanoarray exhibited excellent cathode nitrate reduction to synthesize ammonia Faradaic efficiency and yield (96.5%; 0.5 mmol h -1 cm -2 ) and anodic PET degradation solution to synthesize glycolic acid with Faradaic efficiency and yield (97.5%; 1.4 mmol h -1 cm -2 ). The long-term stability test of the high-entropy nanoarray showed that after 100 hours, the cathode and anode Faraday efficiency and yield remained basically unchanged, indicating that the high-entropy nanoarray has good stability in the new coupling system.

[0050] Embodiment 2:

[0051] A method for preparing a high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion, the method comprising the following steps:

[0052] (1) Immerse a 1.5 cm × 1.5 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0053] (2) Pour 15 mg of solid powders of sodium chloropalladate, 7.5 mg of platinum acetylacetonate, 7.5 mg of nickel chloride hexahydrate, 2 mg of cupric chloride dihydrate, 2 mg of silver trifluoroacetate and 15 mg of tungsten hexacarbonyl into 6 mL of N-N-dimethylformamide solution and ultrasonicate for 15 minutes to dissolve the solid powders. Then, add 1.5 mL of glacial acetic acid and the treated nickel foam to the solution and ultrasonicate for 4 minutes. Then, heat in an oven at 140° C. for 8 hours. After the reaction is completed, wash alternately with water and ethanol solution and dry to obtain a high entropy nanoarray catalyst.

[0054] First, the morphology and structure of the prepared high entropy nanoarrays were characterized by scanning and transmission electron microscopy. The scanning electron microscope image proved that the sample was composed of nanosheet arrays. From the transmission electron microscope image, it was more clearly observed that the high entropy nanoarray was an ultra-thin two-dimensional nanosheet. Further, through the X-ray diffraction pattern, it was observed that a typical single-phase face-centered cubic structure was shown, indicating the formation of a high entropy alloy. The scanning electron microscope energy spectrum shows the uniform distribution of Pd, Pt, Cu, Ni and Ag elements in the high entropy nanoarray. Next, the cathode electrocatalytic nitrate reduction and the anodic electrocatalytic PET degradation liquid oxidation of the high entropy nanoarray and the coupling system performance were investigated respectively. First, through the linear scanning voltammetry curve of nitrate reduction in alkaline, it can be observed that the high entropy nanoarray exhibits a higher current density in the electrolyte with potassium nitrate added, indicating that the high entropy nanoarray has a higher catalytic activity for nitrate reduction. In an electrolyte containing 1M potassium hydroxide + 0.1M potassium nitrate, the high entropy nanoarray has an ammonia yield of 0.52mmol h at a low voltage (-0.15V vs.Hg / HgO). -1 cm -2 , the Faraday efficiency of ammonia reached 96.2%, indicating that the high entropy nanoarray has a better activity in synthesizing ammonia by nitrate reduction. Next, through the linear sweep voltammetric curve of PET degradation solution oxidation under alkaline conditions, it can be observed that the high entropy nanoarray exhibits a higher current density in the PET degradation solution, indicating that the high entropy nanoarray also has a high catalytic activity for the oxidation of PET degradation solution. The glycolic acid yield of the high entropy nanoarray at low voltage (0.8V vs.Hg / HgO) is 1.6mmol h -1 cm -2 , the Faradaic efficiency of glycolic acid reached 97.5%, indicating that the high-entropy nanoarray also has a better activity in the oxidation of PET degradation solution to glycolic acid. Therefore, we tested the electrochemical performance of the high-entropy nanoarray in a new coupling system consisting of cathode nitrate reduction and anode PET degradation solution oxidation. The linear sweep voltammetry curve shows that compared with the traditional water electrolysis, the high-entropy nanoarray only needs a lower voltage to reach the same current density in the new coupling system. In the new coupling system, the high-entropy nanoarray exhibited excellent cathode nitrate reduction synthesis of ammonia Faradaic efficiency and yield (97.5%; 0.6mmol h) at 1V. -1 cm -2 ) and anodic PET degradation solution to synthesize glycolic acid with Faradaic efficiency and yield (98.1%; 1.4 mmol h -1 cm -2 ). The long-term stability test of the high-entropy nanoarray showed that after 100 hours, the cathode and anode Faraday efficiency and yield remained basically unchanged, indicating that the high-entropy nanoarray has good stability in the new coupling system.

[0055] Embodiment 3:

[0056] A method for preparing a high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion, the method comprising the following steps:

[0057] (1) Immerse a 2 cm × 2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use;

[0058] (2) Pour 20 mg of solid powders of sodium chloropalladate, 10 mg of platinum acetylacetonate, 10 mg of nickel chloride hexahydrate, 3 mg of cupric chloride dihydrate, 3 mg of silver trifluoroacetate and 20 mg of tungsten hexacarbonyl into 8 mL of N-N-dimethylformamide solution and ultrasonicate for 20 minutes to dissolve the solid powders. Then, add 2 mL of glacial acetic acid and the treated nickel foam to the solution and ultrasonicate for 5 minutes. Then, heat in an oven at 160° C. for 12 hours. After the reaction is completed, wash alternately with water and ethanol solution and dry to obtain a high entropy nanoarray catalyst.

[0059] First, the morphology and structure of the prepared high entropy nanoarrays were characterized by scanning and transmission electron microscopy. The scanning electron microscope image proved that the sample was composed of nanosheet arrays. From the transmission electron microscope image, it was more clearly observed that the high entropy nanoarray was an ultra-thin two-dimensional nanosheet. Further, through the X-ray diffraction pattern, it was observed that a typical single-phase face-centered cubic structure was shown, indicating the formation of a high entropy alloy. The scanning electron microscope energy spectrum shows the uniform distribution of Pd, Pt, Cu, Ni and Ag elements in the high entropy nanoarray. Next, the cathode electrocatalytic nitrate reduction and the anodic electrocatalytic PET degradation liquid oxidation of the high entropy nanoarray and the coupling system performance were investigated respectively. First, through the linear scanning voltammetry curve of nitrate reduction in alkaline, it can be observed that the high entropy nanoarray exhibits a higher current density in the electrolyte with potassium nitrate added, indicating that the high entropy nanoarray has a high catalytic activity for nitrate reduction. In an electrolyte containing 1M potassium hydroxide + 0.1M potassium nitrate, the high entropy nanoarray has an ammonia yield of 0.60mmol h at a low voltage (-0.15V vs.Hg / HgO). -1 cm -2 , the Faraday efficiency of ammonia reached 96.3%, indicating that the high entropy nanoarray has a better activity in nitrate reduction to synthesize ammonia. Next, through the linear sweep voltammetric curve of PET degradation solution oxidation under alkaline conditions, it can be observed that the high entropy nanoarray exhibits a higher current density in the PET degradation solution, indicating that the high entropy nanoarray also has a high catalytic activity for the oxidation of PET degradation solution. The high entropy nanoarray has a glycolic acid yield of 1.7 mmol h at low voltage (0.8 V vs. Hg / HgO). -1 cm -2, the Faradaic efficiency of glycolic acid reached 98.2%, indicating that the high-entropy nanoarray also has a better activity in synthesizing glycolic acid from PET degradation solution oxidation. Therefore, we tested the electrochemical performance of the high-entropy nanoarray in a new coupling system consisting of cathode nitrate reduction and anode PET degradation solution oxidation. The linear sweep voltammetry curve shows that compared with the traditional water electrolysis, the high-entropy nanoarray only needs a lower voltage to reach the same current density in the new coupling system. In the new coupling system, the high-entropy nanoarray exhibited excellent cathode nitrate reduction synthesis of ammonia Faradaic efficiency and yield (98.1%; 0.7 mmol h) at 1V. -1 cm -2 ) and anodic PET degradation solution to synthesize glycolic acid with Faradaic efficiency and yield (98.5%; 1.5 mmol h -1 cm -2 ). The long-term stability test of the high-entropy nanoarray showed that after 100 hours, the cathode and anode Faraday efficiency and yield remained basically unchanged, indicating that the high-entropy nanoarray has good stability in the new coupling system.

Claims

1. A high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion, prepared by the following method: (1) Immerse 1-2 cm × 1-2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use; (2) Pour 10-20 mg of solid powders of sodium chloropalladate, 5-10 mg of platinum acetylacetonate, 5-10 mg of nickel chloride hexahydrate, 1-3 mg of cupric chloride dihydrate, 1-3 mg of silver trifluoroacetate and 10-20 mg of tungsten hexacarbonyl into 4-8 mL of N-N-dimethylformamide solution and ultrasonicate for 10-20 minutes to dissolve the solid powders. Then, add 1-2 mL of glacial acetic acid and the treated nickel foam to the solution and ultrasonicate for 3-5 minutes. Then, heat in an oven at 120-160° C. for 4-12 hours. After the reaction is completed, wash alternately with water and ethanol solution and dry to obtain a high entropy nanoarray catalyst.

2. A method for preparing a high entropy nanoarray for electrocatalytic nitrate reduction coupled with waste plastic conversion as claimed in claim 1, characterized in that: The method comprises the following steps: (1) Immerse 1-2 cm × 1-2 cm nickel foam in a hydrochloric acid solution to remove the surface oxide layer and oil stains, rinse with deionized water / ethanol three times, and dry for subsequent use; (2) Pour 10-20 mg of solid powders of sodium chloropalladate, 5-10 mg of platinum acetylacetonate, 5-10 mg of nickel chloride hexahydrate, 1-3 mg of cupric chloride dihydrate, 1-3 mg of silver trifluoroacetate and 10-20 mg of tungsten hexacarbonyl into 4-8 mL of N-N-dimethylformamide solution, ultrasonicate for 10-20 minutes to dissolve the solid powders, then add 1-2 mL of glacial acetic acid and the treated nickel foam to the solution, ultrasonicate for 3-5 minutes, and then heat in an oven at 120-160° C. for 4-12 hours; after the reaction is completed, wash alternately with water and ethanol solution, and dry to obtain a high entropy nanoarray catalyst.

3. The method according to claim 2, characterized in that The morphology and crystal structure of the high entropy nanoarray electrocatalyst were controlled by controlling the masses of sodium chloropalladate, platinum acetylacetonate, nickel chloride hexahydrate, cupric chloride dihydrate, silver trifluoroacetate and tungsten hexacarbonyl, the volumes of N-N-dimethylformamide and glacial acetic acid, and the reaction temperature and time.

Citation Information

Patent Citations

  • Flower-like palladium hydride catalyst for catalyzing oxygen reduction reaction and preparation method of flower-like palladium hydride catalyst

    CN113481533A

  • Electrocatalytic nitrate reduction ammonia production catalyst and preparation method and application thereof

    CN115233253A

  • Electroreduction nitrate catalyst, preparation method and synergistic ammonia preparation

    CN117626347A

  • Synthesis method of high-entropy alloy nanostructure and high-entropy alloy nanostructure synthesized by method

    CN118720125A

  • Method for Synthesizing High-Entropy Alloy (HEA) Nanostructures

    US20240328013A1